Smart Door Lock - Mas Erwan, Athirah Nabihah; Muzaffar Alfian, Mohamad Norul Hafiz; Mohamad Adenan, Mohamad Syafiq (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Internet of Things (IoT) has become a phenomenon in many researchers. A smart digital automated system based on IoT plays major role which helps in reducing human work by applying interaction technology in daily life. This research introduces the IoT Smart Door Lock where smartphone uses Wireless Fidelity (Wi-Fi) to activate the door lock. By using Android software, the smartphone will automatically activate the door lock within a specific range. Data transmission will be done using Wi-Fi technology. So, the user does not have to worry whether the door has been locked or not because user can control it by using their smartphone within a specific range. The user also does not have to worry about losing the door key anymore because there is no device required except user’s smartphone. This project consists of hardware and software development. The main purpose on the design is to prevent the situation where the user is unable to unlock the door when the key is missing also to give a solution for users to monitor door status when they forget the door has been locked or not. This system aims to eliminate the use of keys to access the door, where the daily struggle faced to bring along a bunch of keys anywhere. Besides that, the door locking system must function efficiently. The prototype of this system is successfully done, the procedure and the software and hardware requirement has been compiled in this report.